Factors Contributing to Rising Caesarean Section Rates in Garowe, Puntland Somalia (International Journal of Scientific Research and Management (IJSRM), 2025)
This study employed a cross-sectional survey design to assess the demographic characteristics and caesarean section trends among pregnant mothers visiting Dalab Hospital in Garowe, Puntland, Somalia. Using a sample size of 60 respondents, selected through both simple random and purposive sampling techniques, the research explored variables such as age, marital status, education level, occupation, and type of caesarean section. Results revealed a relatively young population, with most women aged 20–39 years, and a high rate of marital experience. Educational levels varied, with secondary education being the most common, though a significant number lacked formal education. Most participants were housewives or businesswomen, indicating high informal economic involvement. Over half of the caesarean deliveries (53.33%) were emergency procedures, highlighting a potential gap in prenatal risk detection and maternal health services. The study concludes that enhancing reproductive health education, improving antenatal care, expanding educational and economic opportunities for women, and strengthening youth-focused and community health interventions are essential to addressing the observed challenges and improving maternal health outcomes in the region.